Study on Preparation and Properties of La0.6Sr0.4Co0.2Fe0.8O3-Δ-mGd0.2Ce0.8O2 (M=0,30,40 and 50) Composite Cathode - Qin Minghan (E3S Web of Conferences, 2023)
Solid Oxide Fuel Cells (SOFCs) can convert chemical energy into electrical energy, with high energy conversion rate, safe operation, no pollutant emissions, and is one of the most potential new energy power generation devices in the future. However, at low and medium temperature (below 800℃), the cathode impedance of SOFCs will increase sharply, resulting in adverse effects on cell performance. Finding cathode materials that can work at low and medium temperature is the key to realize large-scale commercial application of SOFCs. LSCF cathode material is one of the commonly used cathode materials for solid oxide fuel cells because of its excellent electronic and ionic conductivity. However, its cathode performance cannot meet the requirements of commercial applications. At high temperature, solid-state reactions are easy to occur between LSCF and commonly used electrolyte materials such as YSZ, SSZ and LSGM, resulting in the formation of an intermediate phase that is not conducive to Oxygen Reduction Reaction (ORR). In this paper, LSCF and Gd0.2Ce0.8O2 (GDC) were combined by ball milling to prepare composite cathode. XRD test found that the two powders mixed at high temperature did not produce new substances, with good chemical compatibility. The electrical conductivity test showed that the electrical conductivity of the composite LSCF decreased significantly from 227 Sꞏcm-2 at 650℃ to 115, 90 and 77 Sꞏcm-2 at 550℃, respectively. The composite cathode with a composite ratio of 6:4 has the lowest polarization impedance, only 0.10 Ωꞏcm2 at 800℃. The discharge test shows that the cathode with the mass ratio of 6:4 LSCF to GDC has the best performance, and the power density is 328 and 256 mW/cm2 at 800 and 750℃, respectively. The performance of the cathode has good stability after working for 50h.